Narrating life: experiments with human and animal bodies in literature, science and art - Herbrechter, Stefan; Friis, Elisabeth (Experimental practices, 2016)
Narrating-life: in lieu of an introduction / Stefan Herbrechter -- Fiction. From Lives/ David Wagner -- Narrating life in literature. In my core I have the strange impression that I don't belong to the human species: Clarice Lispector's Agua viva as life writing? / Elisabeth Friis -- Charting Solar Systems, Exoplanets and Earth 2.0 / Holly Henry -- Species Encounters: 0. Butler Meets Haraway Meets Deleuze and Guattari / Tom ldema -- Solid-State Fiction: J. G. Ballard and the Crystallization of Life / Moritz Ingwersen -- Dissonance, Data, and DNA: Aesthetics, Biopolitics and Transgenic Music in Richard Powers' Orfeo / Cristina Iuli -- "Chromosomal Cuties", "Fembots", a "Chatty Cyber Trio" or "Cantankerous Clones"? Lynn Hershman Leeson's Teknolust / Tania Nusser -- Submarine Experiments with Human Lives by Chrismoph -- Ransmayr- a waterman narrates / Manuela Rossini -- In Toxicating Languages of Bioinformatic Circulation: Poetics and Other "Smallwork" in The Flame Alphabet / Laura Shackelford -- Life beyond "critique": Murakami after Latour / Jeff Wallace -- Aporias of Survival: Kafka's Alien Incursion / Dominik Zechner -- The Atlas of Man (If by Man We Also Mean Woman) / Steve Tomasula -- Narrating Life in Science. Linear Time and Revolutionary Time: Humans, Apes, and Temporality in Scientific and Literary Narratives / Amelie Bjorck -- Ecolinguistic Activism: How and Why to Rite / Angela Rawlings -- Death Writing: Toward a Bestiary of the Biological Real / Dorion Sagan -- Experimenting with bones / Marianne Sommer -- The Sponge Diver or Bodies on the Seabed / Amalie Smith